The Association Between PM and Depression in China - Guangye He; Yunsong Chen; Senhu Wang; Yiqun Dong; Guodong Ju; Buwei Chen (SAGE Publishing, 2020)
While China has been experiencing unprecedented economic growth, depression is becoming one of the most striking social and mental health problems in recent years. Such a paradox to progress may partially be due to the notoriously poor air quality of the country. To verify this argument, we constructed an index of the prevalence of depression (IPD) using internet search query volumes in Baidu to proxy the potential depression and examined how IPD is associated with PM 2.5 , the major air pollutant in China. Our results from 2-way fixed effects models reveal that a 100 μg·m −3 increase in previous week's PM 2.5 in a city is significantly associated with 0.279 increase in its IPD, comparable to 7.34 hours decrease in weekly daylight, and such relationship is particularly pronounced in the spring and summer and in East and South areas. Our findings of large-scale pattern suggest that PM 2.5 at current levels in China poses serious mental health risks.